Proclaiming the resurrection - Head, Peter M.; Oak Hill College (Cumbria, U.K. Paternoster, 1998)
Includes bibliographical references.
Papers from the First Oak Hill College Annual School of Theology
Keywords: Jesus Christ -- resurrection